2013
DOI: 10.1016/j.econlet.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Are the determinants of CO2 emissions converging among OECD countries?

Abstract: Abstract. This paper studies convergence in CO 2 emission intensity (CO 2 over GDP) among OECD countries over the period 1960-2008 based on its determinants, namely, energy intensity (energy consumption over GDP) and the so-called carbonisation index (CO 2 emissions over energy consumption). We apply the Phillips and Sul (2007) methodology, which tests for the existence of convergence clubs. Our results highlight that differences in emission intensity convergence are more determined by differences in convergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 10 publications
3
54
0
2
Order By: Relevance
“…GDP 2 it is the square of per capita GDP and GDP 3 it refers to the cube of per capita GDP. As in all EKC evaluation studies (e.g., Grossman G M, Krueger A B, 1992 [26]), Equation (12) includes the square per capita GDP and cube per capita GDP, with their coefficients β 2 and β 3 representing the solution of the first-order condition and the second-order condition, which help to evaluate the shape of ECK between pollution and economic development [26]. Different shape of EKC could be found from Figure 5, and the decision rule could be shown as follows:…”
Section: Test Model Construction Of Environment Kuznets Curvementioning
confidence: 99%
See 1 more Smart Citation
“…GDP 2 it is the square of per capita GDP and GDP 3 it refers to the cube of per capita GDP. As in all EKC evaluation studies (e.g., Grossman G M, Krueger A B, 1992 [26]), Equation (12) includes the square per capita GDP and cube per capita GDP, with their coefficients β 2 and β 3 representing the solution of the first-order condition and the second-order condition, which help to evaluate the shape of ECK between pollution and economic development [26]. Different shape of EKC could be found from Figure 5, and the decision rule could be shown as follows:…”
Section: Test Model Construction Of Environment Kuznets Curvementioning
confidence: 99%
“…One area examines carbon dioxide convergence problems, such as the study of Strazicich and List [11], who measured the carbon dioxide emissions from 21 OECD countries from 1960 to 1997 by time series and cross-sectional analysis, and verified the convergence. Camarero et al [12] found that per capita carbon dioxide emissions also converge in OECD countries and demonstrated that their decisive factors are convergence of energy intensity and carbonization index. The other area of study relates to the convergence of sulfur dioxide and nitrogen oxides emissions.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been criticized in the literature due to the assumption that the individual countries' growth rates are likely generated by an autoregressive process of order 1 (AR(1)) and that all permanent cross-economy differences must be completely controlled for (e.g., Friedman 1992;Quah 1993Quah , 1996. This critique has resulted in alternative approaches for testing emission convergence, including the distributional approach to r-convergence (e.g., Quah 1993Quah , 1996Aldy 2006;Camarero et al 2013) and the stochastic convergence approach (e.g., Carlino and Mills 1993;List 1999;Westerlund and Basher 2008). However, since we control for the key country-specific covariates as suggested by theory, we do not expect a significant violation of the assumptions on which the beta convergence approach is based.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the studies in this strand of the literature measures EP either using CO 2 emissions as a ratio of population, CO 2 emissions as a ratio of GDP or energy consumption. Recent papers in this line of research includes: Strazicich and List (2003), Ngugen (2005), Aldy (2006Aldy ( , 2007, Ezcerra (2007), Panopoulou and Pantelidis (2009) Camarero et al (2008), Westerlund and Basher (2008), Brock and Taylor (2010), Camarero et al (2013), and Brännlund et.al (2015). These studies implemented various econometric methods from both parametric and non-parametric approaches to address the question of convergence in environmental performance measured simply as per capita CO 2 emissions, CO 2 emissions as a ratio of GDP or energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have analysed convergence in emissions using variables such as per capita CO 2 emissions (representative papers include Lanne and Liski, 2004;Aldy, 2006Aldy, , 2007Ezcurra, 2007;Westerlund and Basher, 2008;Romero-Ávila, 2008;Chang, 2008 and2009;Barassi et al, 2008 andJobert et al, 2010;Ordás Criado and Grether, 2011) or, in fewer cases, CO 2 emissions over GDP (Camarero et al, 2012). However, most of these studies have only accounted for the environmental side of production processes, i.e., analyses based on variables such as per capita emissions, and/or they have only considered a single emission to represent the impact of economic activity on the environment.…”
Section: Introductionmentioning
confidence: 99%